Integritas Dalam Kepemimpinan Pastoral Berdasarkan Pengajaran Kitab Amsal Tentang Perkataan Dan Sikap Pemimpin - Kamuri, Johanis; Novan (Sekolah Tinggi Theologia Ebenhaezer Tanjung Enim, 2024)
This study aims to describe the characteristics of the pastoral leadership, based on the characteristics of the wise leadership, found in the book of Proverbs. With a qualitative-comparative approach, the authors analyze and describes the various characteristics of wise leader in the book of Proverbs. The characteristics of wise leadership (in the context of public leadership) are used as a conceptual framework to analyze and explain the concept of pastoral leadership, which will be applied in ecclesiastical life. Through this method, the authors show that the teaching of the book of Proverbs about public leadership is very useful for gaining an understanding of the integrity of pastoral leadership, especially in the aspect of the words and attitudes of God's servants. The results of the study show that the teaching of the book of Proverbs about wise words and the attitude of God's servants is very related to his integrity, in carrying out his pastoral leadership. This makes pastoral leadership produce leaders who serve the congregation.